Relative accuracy of spin-image-based registration of partial capitate bones in 4DCT of the wrist. Issue 6 (1st November 2016) - Breighner, Ryan E.; Holmes III, David R.; Leng, Shuai; An, Kai-Nan; McCollough, Cynthia H.; Zhao, Kristin D.
Abstract : In image-based biomechanical analyses, registration transformations are the data of interest. In dynamic four-dimensional computed tomography (4DCT) imaging, the capitate is often partially imaged. While alignment of incomplete objects poses a significant registration challenge, the established spin-image surface-matching algorithm can be utilised to align two surfaces representing disparate but overlapping portions of an object. For this reason, the spin-image algorithm was chosen for the registration of partial bone geometry in 4DCT of the wrist. Registrations were performed on 11 4DCT datasets using complete and partial capitate meshes generated by cropping complete meshes. Relative accuracy was assessed as the difference between partial- and complete-geometry registrations. Accurate registration of partial capitate geometry was achieved with 55% of the proximal capitate geometry on average, and in some cases as little as 35%. Requisite geometry depends on feature salience and imaging resolution; however, the spin-image algorithm should be considered a valuable tool for biomechanists and image analysts.